THE MEASUREMENT OF NURSES’ MENTAL WORKLOAD USING NASA-TLX METHOD (A CASE STUDY) - Nur I; Iskandar H; Ade RF (Malaysian Journal of Public Health Medicine, 2020)
Nurse is a profession that has a quite high workload. It can be seen from how often they should encounter situations which compel them to undergo precisely right decision in saving patients’ lives. Various environmental conditions increase the frustration rate of the nurses, such as noise of the crowds and medical equipment, as well as smell of medicines and wounds at once. Moreover, demands from the patients’ family make it even tougher for them. Therefore, this study aims to measure the mental workload of the nurses at Intensive Care Unit (ICU) and emergency unit (IGD) in the Hospital ZA based on their years of service. The study was conducted using the method of NASA-TLX (National Aeronautics and Space Administration – Task Load Index). It measured the workload in six dimensions: Mental Demand (MD), Physical Demand (PD), Temporal Demand (TD), Own Performance (P), Effort (EF), and Frustration Rate (FR). The results of the study show that the average value of the nurses’ workload at ICU and IGD is in the category very high (respectively 80 and 83) for the nurses with 0-3 years of service, and the most contributing factor for both the primary groups is the effort (EF).